A Novel Multi-attribute Decision Making Methodology and Application (Advances in Systems Science and Applications, 2015)
In the multi-attribute decision making problems, how to effectively extract the decision making rules and rank the schemes are much more important research contents. However, the acquisitions of the decision making rules often are ignored. In view of this, with respect to the problems that there exist a lot of preference information and fuzzy information in the real decision making information system, a novel decision making methodology based on dominance intuitionistic fuzzy rough set is constructed in the paper, and then it is applied to audit risk assessment and risk judgment. Based on the analysis of model and example, the result shows that the proposed model can well realize the extraction of the decision making rules and the ranking of the schemes, and effectively deal with the intuitionistic fuzzy information system with preference information.